Transgenerational Obesity and Alteration of ARHGEF11 in the Rat Liver Induced by Intrauterine Hyperglycemia - Wanyi Zhang; Rina Su; Hui Feng; Li Lin; Chen Wang; Huixia Yang (Journal of Diabetes Research)
It is understood that intrauterine hyperglycemia increases the risk of obesity and diabetes in offspring of consecutive generations but its mechanisms remain obscure. This study is aimed at establishing an intrauterine hyperglycemia rat model to investigate the growth and glycolipid metabolic characteristics in transgenerational offspring and discuss the effects of Rho guanine nucleotide exchange factor 11 (ARHGEF11) and the PI3K/AKT signaling pathway in offspring development. The severe intrauterine hyperglycemia rat model was caused by STZ injection before mating, while offspring development and glycolipid metabolism were observed for the following two generations. The expression of ARHGEF11, ROCK1, PI3K, and AKT was tested in the liver and muscle tissue of F2 offspring. The results showed severe growth restriction in F1 offspring and obesity, fatty liver, and insulin resistance in female F2 offspring, especially the offspring of female intrauterine hyperglycemia-exposed parents (F2G♀C♂) and both (F2G♀G♂). The expression of ARHGEF11 and ROCK1 was significantly elevated; PI3K and phosphorylation of AKT were significantly decreased in liver tissues of F2G♀C♂ and F2G♀G♂. Our study revealed that intrauterine hyperglycemia could cause obesity and abnormal glycolipid metabolism in female transgenerational offspring; the programming effect of the intrauterine environment could cause a more obvious phenotype in the maternal line. Further exploration suggested that increased expression of ARHGEF11 and ROCK1 and the decreased expression of PI3K and phosphorylation of AKT in the liver could be responsible for the abnormal development in F2 offspring.